The effect of systematic couple group therapy on families with depressed juveniles: a pilot trial - Meng, Tian-Jiao; Qian, Ying; Wang, Yu-Lu; Gao, Bing-Ling; Liu, Jia-Jia; Yue, Jing-Li; Tang, Deng-Hua (Frontiers in Psychiatry, 2024)
Background Depression is a primary cause of illness and disability among teenagers, and the incidence of depression and the number of untreated young people have increased in recent years. Effective intervention for those youths could decrease the disease burden and suicide or self-harm risk during preadolescence and adolescence. Objective To verify the short efficacy of the systemic couple group therapy (SCGT) on youths’ depression changes and families with depressed adolescents. Methods The study was a self-control trial; only within-group changes were evaluated. Participants were couples with a depressed child who was resistant to psychotherapy; they were recruited non-randomly through convenient sampling. The paired-sample t-test and Wilcoxon signed-rank test were used to compare differences before and after interventions. The effect sizes were also estimated using Cohen’s d. Spearman’s correlation analysis was used to examine associations between changes. Results A downward trend was seen in depressive symptoms after treatment, and Cohen’s d was 0.33 (p = 0.258). The adolescents perceived fewer interparental conflicts, and the effect sizes were medium for perceived conflict frequency (0.66, p = 0.043), conflict intensity (0.73, p = 0.028), conflict solutions (0.75, p = 0.025), coping efficacy (0.68, p = 0.038), and perceived threat (0.57, p = 0.072). For parents, global communication quality, constructive communication patterns, and subjective marital satisfaction significantly improved after interventions, with large effect sizes (1.11, 0.85, and 1.03, respectively; all p < 0.001). Other destructive communication patterns such as demand/withdraw (p = 0.003) and mutual avoidance (p = 0.018) and communication strategies like verbal aggression (p = 0.012), stonewalling (p = 0.002), avoidance–capitulation (p = 0.036), and child involvement (p = 0.001) also reduced, with medium effect sizes (0.69, 0.52, 0.55, 0.71, 0.46, and 0.79, respectively). Meanwhile, the associations between depression changes and changes in interparental conflicts (p < 0.001) and marital satisfaction (p = 0.001) were significant. Conclusions and clinical relevance The SCGT offers the possibility for the treatment of families with depressed children who are unwilling to seek treatment. Helping parents improve communication and marital quality may have benefits on children’s depressive symptoms.